Functional Properties and Safety Considerations of Zinc Oxide Nanoparticles Under Varying Conditions - Ana Rita Mendes; Carlos M. Granadeiro; Andreia Leite; Otmar Geiss; Ivana Bianchi; Jessica Ponti; Dora Mehn; Eulália Pereira; Paula Teixeira; Fátima Poças (Nanomaterials)
Zinc oxide nanoparticles (ZnO NPs) exhibit diverse morphologies and sizes, influencing their functional properties. However, the relationship between their morphology and behavior under varying conditions remains poorly understood. This study provides novel insights by linking ZnO NPs shape to generation of reactive oxygen species (ROS), and to antimicrobial efficacy under varying temperatures. ROS generation was confirmed via electron paramagnetic resonance, although no antioxidant activity was observed. Antibacterial tests against Escherichia coli and Staphylococcus aureus at different temperatures (4–22 °C) revealed that sheet-shaped NPs achieved complete bacterial reduction (7.5 log CFU mL−1 for E. coli at 4 and 22 °C; 6.8 log CFU mL−1 for S. aureus at 22 °C). Flower-shaped NPs were less effective due to larger size and reduced surface area. Zeta potential ranged from −44 to −58 mV, indicating high stability, with sheet-shaped particles being the most dispersed. Scanning electron microscopy confirmed closer interaction between sheet-shaped NPs and E. coli in agreement with the higher activity. Antibacterial efficacy decreased at 4 °C, highlighting implications for cold storage. The Weibull model successfully described E. coli reduction. These aspects were not previously addressed in the published work. The effect of temperature on the activity and its modeling are new insights into the morphology-dependent antimicrobial activity of ZnO NPs, supporting their integration into packaging materials for food applications.